Gold Nanorods as Saturable Absorber for Harmonic Soliton Molecules Generation - Shu, Yiqing; Guo, Penglai; Li, Xiaohui; Li, Guian; Wang, Peng; Shen, Ge; Li, Jianqing (Frontiers in Chemistry, 2019)
Gold nanorods (GNRs) has been investigated in the field of chemistry, optoelectronics, and medicine because of their tenability, compatibility, electromagnetics and excellent photonics properties. Especially, GNRs, used to generate ultrashort pulse, have been studied recently. However, GNRs based multiple pulses evolution needs to be further explored. In this article, GNRs are synthesized by seed-mediated growth method, characterized systematically and been chosen as SA to apply in ultrafast photonics. The GNRs SA presents a saturable intensity of 266 MW/cm2, modulation depth of 0.6 %, and nonsaturable loss of 51 %. Furthermore, a passively mode-locked erbium-doped fiber laser based on GNRs SA with femtosecond pulse is demonstrated. Thanks to the excellent properties of GNRs, by adjusting the cavity polarization direction with the proposed GNRs SA, soliton molecules operation with spectrum modulation period of 3.3 nm and pulse modulation interval of 2.238 ps is directly obtained. For the most important, 9th-order harmonic soliton molecules have been obtained in the laser cavity for the first time. It is demonstrated that GNRs can be a novel type of nonlinear optical device and have potential applications in the field of ultrafast photonics.